Fentanyl and Dexmedetomidine in Stress Attenuation During Laryngoscopy and Endotracheal Intubation - Shakya, Samir; Singh, Jeevan; Shrestha, Bibek; Chikanbanjar, Sumit (Journal of College of Medical Sciences-Nepal, 2025)
Background Stress response to laryngoscopy and endotracheal intubation leads to stroke, myocardial ischemia, and acute heart failure in high-risk populations. Among various agents, fentanyl and dexmedetomidine are commonly used drugs to blunt the hemodynamic response to laryngoscopy and endotracheal intubation with significant side effects. Objective of this study is to find out the best drug that blunts stress response to laryngoscopy and endotracheal intubation with lesser side effects between fentanyl and dexmedetomidine. Methods One hundred patients planned for elective surgery under general anesthesia were enrolled in this double-blind, observational, cohort, prospective study. Patients were randomly divided into two groups: Group X received 0.5mcg/kg of dexmedetomidine intravenous 10 minutes prior to laryngoscopy via infusion whereas Group Y received 2mcg/kg fentanyl intravenous bolus 5 minutes prior to laryngoscopy. Hemodynamic parameters before and after laryngoscopy and intubation as well as adverse side effects were compared between two groups. Results Dexmedetomidine (0.5mcg/kg) given 10 minutes prior to laryngoscopy was equally effective as fentanyl (2mcg/kg) given 5 minutes prior to laryngoscopy in blunting the hemodynamic response to laryngoscopy and endotracheal intubation. The change in hemodynamic parameters were comparable between two groups. However, 11 patients (out of 14) who developed hypotension were in the fentanyl group. Conclusions Dexmedetomidine (0.5mcg/kg) given 10 minutes prior to laryngoscopy was found to be superior to fentanyl (2mcg/kg) given 5 minutes prior to laryngoscopy. Because dexmedetomidine was associated with lesser side effects and was equally effective as fentanyl in blunting the stress response to laryngoscopy and endotracheal intubation.